Triangulation and Dealing with The Realness of Qualitative Research - Konecki, Krzysztof T. (Qualitative Sociology Review, 2008)
This paper provides a sociologists’ reflection of a sociologist on qualitative field research. Reflections will include some methodological and epistemological considerations that are connected with field work, while building the realness of the description and conclusions, i.e. constructing the quality of qualitative research. The intellectual process of doing research will be characterized by analysis of: description of investigated reality (tales of the field), analytical process, usage of commonsense research procedures (so called triangulation procedures), which are used in the field by the researcher and during analysis or writing a research report to adequately “re – present” researched reality. The three above mentioned stages of representation of reality are interwoven to create one complex intellectual process, which is called “field research”. The quality of qualitative research is the intellectual process where some procedures are used to create the accountability of research conclusions.